TOPICALITY OF CONSIDERATION OF PSYCHOLOGICAL FACTORS IN THE PROCESS OF STRUCTURING MODELS OF ECONOMIC BEHAVIOR - Voskanyan, K. V. (Արդի հոգեբանություն, 2019)
In economic theories, considerable importance is attached to the research connected with the manifestations of the behavior and modelling of different social entities (individuals, reference groups, ethnic groups) as economic entities. Attempts are made to construct effective economic behavioral models by applying mathematical methods. In this context, solutions to problems in which individual and ethno- psychological peculiarities of economic entities act as factors have become relevant in psychology. It is assumed that economic activity which takes into account psychological peculiarities of different social layers of society can contribute to the formation of balanced inter-communal economic relations, which, in its turn, can prevent the process of economic stratification, containing antagonistic elements, and keep the society away from political shocks.